Multivalently meromorphic functions with two fixed points defined by Srivastava-Attiya operator - Vijaya, Kaliyappan; Kasthuri, Murugesan (Global Journal of Mathematical Analysis, 2014)
In the present investigation we definea new class of meromorphic functions on the punctured unit disk U^*:= {zC: 0<|z|<1} by making use of theSrivastava-Attiya operator. Coefficient inequalities, growth and distortion inequalities, aswell as radii of meromorphically starlikeness are obtained. We also establish someresults concerning the convolution products and inclusion results.Keywords: Convolution(Hadamard product),Hurwitz-Learch zeta function, Integral operator, Meromorphic functions,Starlike function,Convex function.